Design and FPGA based Implementation of IEEE 1588 Precision Time Protocol for Synchronisation in Distributed IoT Applications. Issue 1 (2nd January 2022) - Nagra, Aamir Sohail; Allahi, Irfan; Pasha, Muhammad Adeel; Masud, Shahid
ABSTRACT: In distributed network applications such as the Internet of Things (IoT), a master clock is used to provide a frame of reference among all constituent nodes. Any drift in the clock on a single node can cause serious cascading effects in a system that largely involves ordered events and time-critical tasks. To provide a stable reference clock, time synchronisation protocols are utilised in distributed systems where client nodes can synchronise their clock with a master node. IEEE 1588 Precision Time Protocol (PTP) is increasingly being used to provide high time synchronisation accuracy in comparison with other synchronisation protocols. In this paper, we have proposed a hardware design and FPGA-based implementation of the IEEE 1588 protocol to be used in wired LAN communication. Experimental results show synchronisation accuracy in the range of few nanoseconds, which is significantly better than the existing implementations. The FPGA implementation was carried out on a Xilinx Artix-7 evaluation board.